75 EFFECTS OF RENAL ARTERY STENTING ON KIDNEY FUNCTION AND BLOOD PRESSURE IN PATIENTS WITH ATHEROSCLEROTIC RENAL ARTERY DISEASE: OUR EXPERIENCE. (1st March 2006) - Padigala, K. K.; Pechitty, S. S.; Frem, G. J.
Abstract : Purpose of Study: Earlier studies have shown that renal artery stent revascularization in the presence of atherosclerotic renal artery disease has a beneficial effect on blood pressure (BP) control and renal function, while some authors have reported that stent revascularization has minimal or no effect on kidney function. We did a retrospective chart review of the effect of stenting in our patient population with atherosclerotic renal artery stenosis. Methods: This study involved 18 patients who underwent stent placement for atherosclerotic renal artery stenosis between 1999 and 2004 in our facility. The most common indication for the procedure was a combination of uncontrolled hypertension requiring three or more medications and worsening renal function. Patients whose serum creatinine was greater than 4.0 mg/dL at the time of stenting were excluded from the study. Renal function was estimated by calculating the glomerular filtration rate (GFR) using the MDRD equation. BP and GFR were recorded just before the procedure and at regular 3-month interval follow-up visits at the outpatient clinic up to 1 year. Differences in GFR and BP at baseline and 1 year after the procedure were compared for statistical significance using the Wilcoxon matched pairs sign rank test. A p value < .05 was considered statistically significant. The institutional review board of our hospital approved the study protocol. Results: Mean age of our study population was 74 ± 14 years and 70% of patients also had diabetes mellitus type 2. At 1 year after the procedure mean systolic blood pressure decreased from 143 mm Hg at baseline to 131 m mHg (p = .05). Mean diastolic blood pressure decreased from 76 mm Hg to 67 mm Hg (p = .006) and the mean arterial pressure decreased from 98 mm Hg to 88 mm Hg (p = .0195). Further, the mean GFR decreased from 38.14 mL/min/1.73 sq.m to 35.16 mL/min/1.73 sq.m (p = .2634). Conclusions: Significant improvement was noted in the blood pressure variables in patients who were treated with stent deployment. There was a small but statistically nonsignificant decrease in GFR; perhaps improved blood flow and blood pressure control helped stabilize kidney function in the face of underlying diseases such as diabetes. Our findings support a clinically important and statistically significant decline in blood pressure following stenting of atherosclerotic renal artery stenosis. However, in contrast to some previous studies, no significant improvement was noted in the renal function.